2010
DOI: 10.1111/j.1472-8206.2009.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic‐like effect of Carvacrol (5‐isopropyl‐2‐methylphenol) in mice: involvement with GABAergic transmission

Abstract: Carvacrol (5-isopropyl-2-methylphenol) is a monoterpenic phenol present in the essencial oil of many plants. It is the major component of the essential oil fraction of oregano and thyme. This work presents the behavioral effects of carvacrol in animal models of elevated plus maze (EPM), open field, Rotarod and barbiturate-induced sleeping time tests in mice. Carvacrol (CVC) was administered orally, in male mice, at single doses of 12.5; 25 and 50 mg/kg while diazepam 1 or 2 mg/kg was used as standard drug and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 32 publications
9
69
0
1
Order By: Relevance
“…Although this indicates a central depressant effect of carvacrol, it was observed only the highest dose used and the first time point investigated in spontaneous locomotor test, while the antihypernociceptive effect of this compound was also demonstrated at the lower doses used in this study. Of interest, our previous study demonstrated that carvacrol does not promote alteration of performance in the Rotarod test and neither on open field (Melo et al 2010b). Taken altogether, these observations confirm that the anti-hypernociceptive actions of carvacrol observed in this study are not entirely due to an inhibitory effect on the CNS.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although this indicates a central depressant effect of carvacrol, it was observed only the highest dose used and the first time point investigated in spontaneous locomotor test, while the antihypernociceptive effect of this compound was also demonstrated at the lower doses used in this study. Of interest, our previous study demonstrated that carvacrol does not promote alteration of performance in the Rotarod test and neither on open field (Melo et al 2010b). Taken altogether, these observations confirm that the anti-hypernociceptive actions of carvacrol observed in this study are not entirely due to an inhibitory effect on the CNS.…”
Section: Discussionsupporting
confidence: 82%
“…This monoterpene has also presented an anticonvulsant property , besides anxiolytic (Melo et al 2010b) and antidepressant (Melo et al 2011a) effects with involvement of GABAergic transmission and the dopaminergic system, respectively. Furthermore, local application of carvacrol gel is able to protect against tissue damage in ligature-induced periodontitis in rats, probably by its inhibitory effect on periodontal pathogens (Botelho et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Type A α-aminobutyric acid (GABAA) receptors are the major inhibitory neurotransmitter receptors in the Central Nervous System, which is involved in epilepsy, sedation and anxiolysis, producing these effects through binding to GABAA receptors (Melo et al, 2010). Anxiolytics facilitate the coupling of GABAergic receptors to GABAA and produce their pharmacological effect by binding to a benzodiazepine recognition site on the GABAA receptor complex (Harris et al, 2008;Ennaceur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the activity of orcinol is not only as an aglycone of OG, but also based on the findings of our review on the bioactivity of some small-molecule natural phenols (constructed only with C, H, and O; M w 5300). These small phenols, including but not limited to sesamol (Kumar et al, 2013), carvacrol (Melo et al, 2010), gallic acid (Dhingra et al, 2012), 4-hydroxybenzaldehyde (Jung et al, 2006), paeonol (Mi et al, 2005), and caffeic acid (Takeda et al, 2003), have been reported to have anxiolytic properties. The conservative hydroxyl group in diverse structures indicates that phenol moiety undertakes a pharmacological role.…”
Section: Discussionmentioning
confidence: 99%